A thousand shades of green : sustainable strategies for competitive advantage - Winsemius, Pieter (Earthscan Publications, 2002)
"What does it mean for the environment?" is a strategic corollary of almost any significant business decision today, and companies must take seriously their responsibilities to regulators, customers, employees and the wider society. "A Thousand Shades of.